Structural dynamics of precursor and product of the RNA enzyme from the hepatitis delta virus as revealed by molecular dynamics simulations - Krasovska, Maryna V; Sefcikova, Jana; Spacková, Nad'a; Sponer, Jirí; Walter, Nils G (Journal of molecular biology, 2005)
The hepatitis delta virus (HDV) ribozyme is a self-cleaving RNA enzyme involved in the replication of a human pathogen, the hepatitis delta virus. Recent crystal structures of the precursor and product of self-cleavage, together with detailed kinetic analyses, have led to hypotheses on the catalytic strategies employed by the HDV ribozyme. We report molecular dynamics (MD) simulations (approximately 120 ns total simulation time) to test the plausibility that specific conformational rearrangements are involved in catalysis. Site-specific self-cleavage requires cytidine in position 75 (C75). A precursor simulation with unprotonated C75 reveals a rather weak dynamic binding of C75 in the catalytic pocket with spontaneous, transient formation of a H-bond between U-1(O2') and C75(N3). This H-bond would be required for C75 to act as the general base. Upon protonation in the precursor, C75H+ has a tendency to move towards its product location and establish a firm H-bonding network within the catalytic pocket. However, a C75H+(N3)-G1(O5') H-bond, which would be expected if C75 acted as a general acid catalyst, is not observed on the present simulation timescale. The adjacent loop L3 is relatively dynamic and may serve as a flexible structural element, possibly gated by the closing U20.G25 base-pair, to facilitate a conformational switch induced by a protonated C75H+. L3 also controls the electrostatic environment of the catalytic core, which in turn may modulate C75 base strength and metal ion binding. We find that a distant RNA tertiary interaction involving a protonated cytidine (C41) becomes unstable when left unprotonated, leading to disruptive conformational rearrangements adjacent to the catalytic core. A Na ion temporarily compensates for the loss of the protonated hydrogen bond, which is strikingly consistent with the experimentally observed synergy between low pH and high Na+ concentrations in mediating residual self-cleavage of the HDV ribozyme in the absence of divalents.
Keywords: RNA, Catalytic; RNA, Viral; sekvence nukleotidů; RNA virová; krystalografie rentgenová; Nucleic Acid Conformation; Thermodynamics; Static Electricity; vodíková vazba; prekurzory RNA; protony; molekulární modely; Crystallography, X-Ray; virus hepatitidy delta; Models, Molecular; termodynamika; konformace nukleové kyseliny; Hepatitis Delta Virus; RNA Precursors; lidé; Catalytic Domain; statická elektřina; Humans; Protons; Base Sequence; Hydrogen Bonding; katalytická doména; RNA katalytická